Analyzing the Contributions of the Sri Lanka Muslim Congress and its Founder–Leader to Muslim Politics and Community in Sri Lanka - Mohammad Agus Yusoff; Athambawa Sarjoon; Nordin Hussin; Azhar Ahmad (Social Sciences, 2017)
Historically, the politics of Sri Lankan Muslims has been identified as moderate and characterized by alliance-making with other major ethnic groups. Muslims rarely considered to form a strong political movement or party to increase their political influence, until the peak of the civil war in the 1980s. This occurrence helped the Muslim community to be facilitated socially and economically, but it also made them vulnerable in terms of rights and power accommodation in national politics. However, the establishment of the Sri Lanka Muslim Congress (SLMC) and its distinct form of politics progressively revived the Muslim community and its politics. This study examines the contributions of SLMC and its founder–leader to Muslim politics and community in Sri Lanka. The findings of this study reveal that SLMC under its founder–leader uniquely colored Muslim politics, which in turn strengthened popular support and transformed the Muslim community into “queen-makers” in the national politics. Under its founder–leader Mohammed Hussain Mohammed Ashraff, the SLMC greatly contributed to the transformation of Muslim political culture, and to the uplift of the socio-cultural, economic, and political status of the Muslim community, while voicing Muslims’ grievances and fighting for their status, rights, powers, and privileges. By contrast, the party and its founder–leader faced considerable opposition and criticisms on communal and racial bases. Nonetheless, the qualities and contributions of its founder–leader continue to be remembered and still have a significant influence on Muslims politics in Sri Lanka.